Novel pectin and nanocellulose based bioinks for 3D bioprinting applications - Guincho, Pedro Batalha (2023)
The implementation of personalized and efficient strategies for damaged tissue/organ replacement is becoming increasingly urgent, being observed significant advancements in the field of tissue engineering in recent years, namely in 3D bioprinting of functional living tissue analogues. This automatized technology allows a wide control over the cellular environment and the overall tissue organization. To obtain a fully developed and functional tissue/organ, the bioprinting method and the bioink need to have adequate properties and functionalities, for this reason, a thoughtful choice is crucial. Recently, there have been great developments in the field of bioinks for bioprinting applications. However, the developed bioinks still present several limitations, such as weak mechanical properties, low viability, or high production costs. In this context, the objective of this dissertation is the development of a pectinnanocellulose fibers hydrogel-based bioink laden with human keratinocyte cells (HaCaT cells) for 3D bioprinting. These biopolymers were chosen due to their great potential for 3D bioprinting applications. Pectin is biodegradable, hydrophilic, and can form hydrogels in the presence of divalent cations, such as calcium. Nanocellulose has also already demonstrated its potentialities in 3Dbioprinting, revealing excellent mechanical properties and biocompatibility. However, this combination of biopolymers has never been explored for 3Dbioprinting. The developed bioinks were characterized in terms of their rheology, chemical structure/composition, and morphology. Furthermore, the bioprinting parameters were optimized and the cytotoxicity of the hydrogels evaluated. Rheologically, the inks presented a shear-thinning behavior, which is extremely important for 3D bioprinting applications, furthermore, an increase of three levels of magnitude in viscosity and shear stress was observed after a pre-crosslinking procedure. The inks were able to be printed with the optimal result being obtained for the ink with the highest content of NFC and prereticulated with 1% (m/v) CaCl2, which allowed the printing of up to 8 layers without losing resolution. The fully-crosslinked hydrogels were considered noncytotoxic towards HaCaT cells, however higher cell viability values were observed for the hydrogels with higher NFC content. This study can be considered a great step towards the use of pectin-NFC-based bioinks in 3Dbioprinting applications.